Search for Antiviral Preparations in Series of New Derivatives of N-Substituted Piperidines - Gulmira S. Akhmetova; Ulzhalgas B. Issayeva; Kaldybay D. Praliyev; Ilya S. Korotetskiy; Tulegen M. Seilkhanov; Samir A. Ross; Manas T. Omyrzakov; Ubaidilla M. Datkhayev; Khaidar S. Tassibekov; Lyudmila N. Ivanova; Natalya V. Zubenko (Molecules)
Cyanohydrin synthesis, as the simplest preparative method for introducing a carboxyl group into a piperidine molecule, has been used to obtain potentially biologically active piperidinecarboxylic acids, which have alkyl and arylalkyl radicals at the nitrogen atom of the piperidine ring. Hydrochlorides of cyclopropanecarboxylic acid esters based on piperidinecarboxylic acids, as well as hydrochlorides of fluorobenzoic acid esters of N-substituted piperidines, have been synthesized. The purpose of this study was to search for antiviral drugs among new piperidine derivatives. The structure of the synthesized compounds was studied by NMR methods, including COSY (1H-1H), HMQC (1H-13C) and HMBC (1H-13C) techniques. The values of chemical shifts, multiplicities, and integrated intensities of 1H and 13C signals in one-dimensional NMR spectra were determined. The results of COSY (1H-1H), HMQC (1H-13C), and HMBC (1H-13C) revealed homo- and heteronuclear interactions, confirming the structure of the studied compounds. The antiviral and cytotoxic activities of the synthesized compounds were studied. The antiviral activity in vitro was determined according to the therapeutic regimen against the influenza A/Swine/Iowa/30 (H1N1) virus on the MDCK cell model. The cytotoxicity of the studied substances in vitro was assessed using the MTT test. Based on the results of the antiviral activity against the influenza A virus, it can be concluded that all substances are effective against the influenza A/H1N1 virus compared to the commercial preparations Tamiflu and Rimantadine.